Specificity in LSP - Thomas N. Huckin (Ibérica, 2003)
The defining feature of our field is the teaching and use of language for specific purposes. Not surprisingly, this has led to a debate over just how specific those purposes should be. The debate is longstanding, stirred initially by Hutchinson and Waters' classic 1980 article, 'ESP at the Crossroads' and reinvigorated most recently by Hyland (2002), who argues that the field has drifted away from specificity, becoming too generalized and diffuse. This paper lays out the arguments on both sides and then stakes out a position that draws from each of them. While agreeing with some of Hyland's criticisms of the 'wide-angle' position (for example, that generalized LSP can fail to appreciate the distinct linguistic and rhetorical features of specialized discourses), the paper criticizes his 'narrow-angle' position as well by pointing out that it can easily lead to a teacher-centered prescriptivism and to an overly rigid focus on certain forms and tasks at the expense of others. Furthermore, such an approach fails to prepare students for the unpredictable new forms of communication that await them in their professional careers. In general, a teachercentered approach, no matter how specific, is unlikely to have the pedagogical effectiveness of a student-centered approach, especially in heterogeneous classes. Specificity, it is argued, must ultimately be supplied by the student, not by the teacher, for it is the student more than the LSP teacher who is in the process of becoming an insider and whose interests are best served by becoming an astute analyst of the specialist discourse. The teacher's role should be that of facilitator, instructing students in analytic strategies, both rhetorical and textual. The paper concludes with a number of illustrations in how this can be done, drawing especially on work in genre study.